"Airplanes Not Walls": Broaching Unauthorized (Im)migration and Schooling in Mexico. Issue 8 (August 2020) - Gallo, Sarah; Ortiz, Andrea
Background/Context: This article builds on U.S.-based research on undocumented status and schooling to examine how an elementary school teacher in Mexico successfully integrates transnational students' experiences related to unauthorized (im)migration into the classroom. Purpose/Objective/Research Question/Focus of Study: Drawing on a politicized funds of knowledge framework, we focus on an exceptional fifth-grade teacher's curricular, pedagogical, and relational decisions to provide concrete examples of how educators on both sides of the border can carefully integrate students' politicized experiences into their classrooms. Setting: This research took place in a semirural fifth-grade classroom in Central Mexico during the 2016–2017 academic year, when Donald Trump was elected president of the United States. Population/Participants/Subjects: This article focuses on the routine educational practices within a single fifth-grade classroom in a highly transnational Central Mexican town. Participants included a binational student who had recently relocated to Mexico because of U.S.-based immigration policies, her peers from transnational families with ties to the United States, and their fifth-grade teacher. Research Design: This school-based ethnographic study involved weekly participant observation and video recording of routine activities in Profe Julio's fifth-grade classroom during the 2016–2017 academic year. Observations were triangulated with additional data sources such as interviews (with educators, binational students, and binational caregivers) and artifacts (such as homework assignments and student writing). Findings/Results: Through a close examination of a fifth-grade classroom in Mexico, we illustrate how the teacher brought students' (im)migration experiences into school by leveraging openings in the curriculum, developing interpersonal relationships of care, and engaging in a range of pedagogical moves. Conclusions/Recommendations: We discuss how this teacher's educational practices could be carefully tailored to U.S. classrooms within the current anti-immigrant context. These practices include building relationships of care, looking for openings in the curriculum, providing academic distance, prioritizing teachers as learners, and working with school leadership for guidance on navigating politicized topics under the current U.S. administration.